Improved anti-corrosion performance of epoxy coatings based on pH-sensitive gels loaded with inhibitors - Bo Fang; Xinyue Zhang; Hongliang Liu; Fangchao Zhao; Yuzhu Li; Xiaotong Zeng; Zhenliang Feng; Wenzuo Li; Jie Liu (Journal of Materials Research and Technology)
The pH-sensitive Tannic acid@ Benzotriazole@ Poly (hydroxypropyl acrylate-triethoxyvinylsilane -acrylic acid)/polyethyl enimide (TBP) gels loaded with corrosion inhibitors and the modified TBP composite coatings (TBP/EP coatings) were prepared innovatively. The TBP gels possessed excellent pH-sensitive properties and compatibility with epoxy coatings. Furthermore, the protective performance of the TBP/EP coatings was improved by the addition of TBP gels, which was attributed to the TBP gels filling the defects of the coatings after expansion of water absorption, and the released corrosion inhibitors formed the corrosion inhibitor films and the iron tannate films on the metal surface, respectively. Following the 181d immersion test, the TBP/EP coatings sustained an impedance value of 2.36 × 107 Ω cm2. In contrast, the impedance value of the epoxy coatings decreased to 6.86 × 104 Ω cm2. In comparison to epoxy coatings, the TBP/EP coatings demonstrated a notable enhancement in original adhesion and wet adhesion, with increases of 18.21% and 74.7%, respectively. In the end, the TBP/EP coatings corrosion inhibition functions were innovatively introduced.